(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Fruit drying system project mainly based on the drying of the dry-fruits. In today world due to increases of population demand of dry-fruits are increased. So that point of view we need to dry fruit in the short duration. In conventional sun drying process more time is required for the drying of the fruit. So we can use fruit drying system. In this system consist one metal chamber to drying fruit. The air is blown inside the chamber and exhaust fan are placed to air in and out. The nickel chrome coil is used for the heating purpose of the chamber. By using microprocessor we can control all the process like the heating of the coil, sensing of the metal body temperature and the humidity control. The automatic fruit drying system is very applicable for the drying fruit in the short duration of the time. Fruit drying system project is mainly based on the agriculture field.